The Readiness of Consumers to Adopt Green Hotels in Indonesia: Does Trust Matter? - Gunawan, Theresia; Erlina, Magdalena; Subari, Fransiska Anita (Indonesian Journal of Sustainability Accounting and Management, 2023)
The number of hotels and consumers that are concerned about the green concept has been increasing, on the other hand, consumers are also becoming skeptical towards the practice of greenwash. Due to the limited availability of research regarding trust in green hotels in developing countries, the purpose of this study is to examine how the influence of attributes on green hotels can affect attitude, intention to stay, and willingness to pay a premium price, as well as how trust can mediate this relationship. The data were collected through a purposive sampling survey of 152 hotel consumers in Indonesia who could identify 5 of the 15 features of green hotels. The data were analyzed using the partial least squares method. The results confirm that the green hotel attributes do not affect the willingness to pay premium prices either with the existence or the absence of trust as a mediating factor. However, this research reveals that consumer trust is essential because it can be a mediating factor that can raise the willingness to stay at green hotels. This research is valuable to provide insight for hotel managers to develop strategies to increase the trust and sales of targeted green customers.